Innovation in Making Wet Noodles from Local Ingredients: Assistance to The Use of Natural Coloring in The PKK Community in Nagari Padang Toboh Ulakan - Wellyalina, Wellyalina; Games, Donard; Kurnia Sari, Dessy (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2024)
Nagari Padang Toboh Ulakan in Pariaman Regency faces the challenge of low education with the majority of the population having only completed basic education. Focus on earning income replaces interest in pursuing higher education. However, local agriculture has not had a significant economic impact, and the lack of product marketing become a problem. Community empowerment programs, including hydroponic gardening, are one solution to this problem. The PKK community has vegetables such as pakcoy that have not been utilized optimally. In discussions, the processing of pakcoy into noodles has not been optimally successful. In fact, pakcoy can be a healthy natural coloring for noodles. The training aims to increase PKK community’s knowledge about the use of natural pakcoy coloring in noodles. Various methods are applied, ranging from education, training, to demonstrations. After the training, there was increased understanding and innovation in pakcoy processing, improving the nutritional value and appearance of the noodles. Discussions with resource persons help understand the stages of serving noodles according to standards. Training also improves knowledge of the right ingredients for noodles and product storage skills. This activity provides a broad understanding of the use of natural pakcoy coloring in noodles. Apart from improving the quality of noodle products, it also contributes to better marketing and improving the economic welfare of local communities